Brain Responses in CFS and TMD to Autonomic Challenges: An Exploratory fMRI Study. (July 2020) - Vuong, Q.C.; Allison, J.R.; Finkelmeyer, A.; Newton, J.; Durham, J.
Introduction: Dysfunction of the autonomic nervous system (ANS) is seen in chronic fatigue syndrome (CFS) and temporomandibular disorders (TMDs). Both conditions have poorly understood pathophysiology. Several brain structures that play a role in pain and fatigue, such as the insular cortex and basal ganglia, are also implicated in autonomic function. Objectives: ANS dysfunction may point to common neurophysiologic mechanisms underlying the predominant symptoms for CFS and TMD. No studies to date have investigated the combination of both conditions. Thus, our aim was to test whether patients with CFS with or without TMD show differences in brain responses to autonomic challenges. Methods: In this exploratory functional imaging study, patients with CFS who screened positive for TMD (n = 26), patients who screened negative for TMD (n = 16), and age-matched control participants (n = 10) performed the Valsalva maneuver while in a 3-T magnetic resonance imaging scanner. This maneuver is known to activate the ANS. Results: For all 3 groups, whole-brain F test showed increased brain activation during the maneuver in the superior and inferior frontal gyri, the left and right putamen and thalamus, and the insular cortex. Furthermore, group contrasts with small-volume correction showed that patients with CFS who screened positive for TMD showed greater activity in the left insular cortex as compared with patients who screened negative and in the left caudate nucleus as compared with controls. Conclusion: Our results suggest that increased activity in the cortical and subcortical regions observed during autonomic challenges may be modulated by fatigue and pain. ANS dysfunction may be a contributing factor to these findings, and further work is required to tease apart the complex relationship among CFS, TMD, and autonomic functions. Knowledge Transfer Statement: Brain activity related to activation of the autonomic nervous system in patients with chronic fatigue syndrome who screened positive for painful temporomandibular disorder was greater than in patients who screened negative; activity was seen in brain regions associated with autonomic functions and pain. These findings suggest that autonomic dysfunction may play a role in the pathophysiology of both conditions, explain some of the apparent comorbidity between them, and offer avenues to help with treatment.